Evaluation of the clinical-functional vulnerability index in older adults - Arthur Alexandrino; Ellen Karolaine Lucena da Cruz; Pedro Yan Dantas de Medeiros; Caio Bismarck Silva de Oliveira; Djaine Silva de Araújo; Matheus Figueiredo Nogueira (Revista Brasileira de Geriatria e Gerontologia, 2020)
Abstract Objective: To evaluate the clinical-functional vulnerability index (CFVI) of older adults and its relationship with socioeconomic, behavioral, clinical and therapeutic indicators. Method: A cross-sectional epidemiological study with a quantitative design was performed with 318 randomly drawn older adults registered with the Family Health Strategy. Data were collected through the CFVI-20 questionnaire and analysis was supported by descriptive, bivariate and multivariate statistics, with results with p-value <0.05 considered significant. Results: most older adults (59.1%) were considered frail or potentially frail. Among the groups studied, there was a statistically significant difference in the CFVI for the variables age group (p<0.001), functional literacy (p=0.001), alcohol consumption (p<0.001), physical exercise (p<0.001), self-reported health problems (p<0.001) and medication use (p<0.001), as well as a positive correlation with stress (r=0.135; p=0.016). In the multiple linear regression model, the set of sociodemographic predictor variables explained the frailty of the elderly by 30.4% (R2=0.304). Conclusions: The advancement of age, as a non-controllable variable, indicates a need to encourage the maintenance of functionality in old age, based on the health care strategies that prolong longevity with safety, autonomy and vitality.